2012
DOI: 10.3122/jabfm.2012.05.120141
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned and Challenges Ahead: Report from the OCHIN Safety Net West Practice-based Research Network (PBRN)

Abstract: Introduction We recently completed a strategic planning process to better understand the development of our five-year-old PBRN and to identify gaps between our original vision and current progress. While many of our experiences are not new to the PBRN community, our reflections may be valuable for those developing or re-shaping PBRNs in a changing health care environment. Lessons Learned We learned about the importance of: (1) Shared vision and commitment to a unique patient population; (2) Strong leadership… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 9 publications
0
34
0
Order By: Relevance
“…Yet, best practices for developing these data-sharing networks are not well understood. DeVoe et al (2012) reported on developing the OCHIN SafetyNet West Practice-Based Research Network (Patient-Centered Outcomes Research Institute, n.d.) and identified challenges in governance of data infrastructure and engaging busy clinicians. Although these are similar to our identified challenges, we had the additional challenge of implementing our infrastructure across practices with disparate EHR systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, best practices for developing these data-sharing networks are not well understood. DeVoe et al (2012) reported on developing the OCHIN SafetyNet West Practice-Based Research Network (Patient-Centered Outcomes Research Institute, n.d.) and identified challenges in governance of data infrastructure and engaging busy clinicians. Although these are similar to our identified challenges, we had the additional challenge of implementing our infrastructure across practices with disparate EHR systems.…”
Section: Discussionmentioning
confidence: 99%
“…The Institute of Translational Health Sciences, with its commitment to developing tools that speed translation of discoveries into clinical practice, has supported the development of Data QUEST. This approach may be applicable to many PBRNs affiliated with institutions granted Clinical Translational Science Awards (DeVoe et al, 2012). Determining funding streams that allow for flexibility and nimbleness in the initial rollout of data-sharing infrastructures is critical to success, as is developing ongoing resources for maintenance and growth of the infrastructures.…”
Section: Discussionmentioning
confidence: 99%
“…These clinics are members of the OCHIN Inc., practice-based research network, and share a common EHR 20 , 21. We observed clinic operations and conducted one-on-one, semi-structured interviews with five to seven people at each clinic ( N = 26).…”
Section: Methodsmentioning
confidence: 99%
“…14 OCHIN invested a large amount of its CHARN funding to augment its PBRN staff and clinic champions for research at the clinics most involved with the PBRN. The tangible fruit of that investment is a significantly stronger capacity for provider-researcher communication and “matchmaking” between providers and researchers, which was achieved in 2 ways.…”
Section: Ochin: Enhancing a Pbrn’s Ability To Conduct Clinician-drivementioning
confidence: 99%